The 1st International Conference on Computational Engineering and Intelligent Systems 2022
DOI: 10.3390/engproc2022014004
|View full text |Cite
|
Sign up to set email alerts
|

Backstepping Control of Drone

Abstract: This work derives the models which can be used to design and implement control laws for six degrees-of-freedom (DOF) quadrotor stability. The first part of this paper deals with the presentation of the background of quadrotor modeling; the second part describes the direct control of the drone using the backstepping control principal. This principal is based on the division of the system into several sub-systems in a cascade, which makes the control laws generated on each subsystem, in a decreasing manner, unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Quadrotor's movement may be split into 2 control systems: a rotating sub-system (roll, pitch, and yaw) and a translating sub-system (x, y, and z coordinates). The revolving sub-system is completely actuated whilst translating sub-system is under-actuated [37]. Newton Euler equation can be formulated by (3):…”
Section: Quadrotor Dynamicsmentioning
confidence: 99%
“…Quadrotor's movement may be split into 2 control systems: a rotating sub-system (roll, pitch, and yaw) and a translating sub-system (x, y, and z coordinates). The revolving sub-system is completely actuated whilst translating sub-system is under-actuated [37]. Newton Euler equation can be formulated by (3):…”
Section: Quadrotor Dynamicsmentioning
confidence: 99%
“…The authors in [7], [9], [10], [11] derived the quadcopter mathematical model and employed a linearized optimal Proportional-Integral-Derivative (PID) controller to track the desired trajectory, while both of the authors in [12], [13] used a Linear Quadratic Regulator (LQR) controller. The authors in [14], [15], [16], [17] utilized the optimal nonlinear Backstepping Controller (BSC), and the authors in [18], [19], [20]proposed an optimal Integral Backstepping Controller (IBSC) to control the attitude and altitude of the quadcopter. The authors in [21], [22], [23] suggested the Sliding Mode Controller (SMC), while the authors in [24], [25], [26] proposed the Integral Sliding Mode Controller (ISMC) for tracking the desired trajectory with high robustness.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the widely used quad-rotor helicopter attitude control methods mainly include PID control [13][14][15], sliding mode control [16][17][18], backstepping control [19][20][21], neural network control [22,23], active disturbance rejection control (ADRC) [24][25][26][27] and so on. PID control is composed of proportional, integral and differential parts.…”
Section: Introductionmentioning
confidence: 99%